Public finance management using artificial intelligence (Journal of Economic Research & Business Administration, 2025)
The article explores the use of artificial intelligence (AI) elements in public finance management. In 2025, the President and the Government of the Republic of Kazakhstan set the task for government agencies and national companies to implement AI tools in their activities. However, despite the growing interest in artificial intelligence, the issue of its integration into the public financial management system in Kazakhstan has so far been covered to a limited extent and requires further study. This highlights both the scientific novelty and the practical significance of the research. The relevance of the topic is confirmed by the need to increase the efficiency and transparency of budget processes in the context of digitalization of the public sector.The problem of the study is determined by the lack of efficiency and transparency of the budget process, which creates risks of insufficient budget resources and fiscal imbalance. The object of the research is the public finance management system of Kazakhstan, and the subject is the integration of artificial intelligence methods into budget planning, execution, monitoring and risk assessment processes.The purpose of the study is to substantiate and develop methodological approaches to the introduction of artificial intelligence and neural network modeling into the public financial management system of the Republic of Kazakhstan, aimed at optimizing the budget process, improving the efficiency of planning, execution and control of budget expenditures, as well as ensuring transparency and countering corruption risks in the context of digitalization of public finances.The hypothesis of the study is that the use of AI models in public finance management will improve the efficiency of budget planning and disbursement, improve risk assessment and increase transparency of fiscal processes.The methodological basis of the research consisted of systematic, logical and comparative analysis, methods of observation, grouping, synthesis, as well as statistical and expert assessment methods. Based on the assessment of the main functional elements of public finance management, ways are proposed to improve the efficiency of planning and disbursement of public budget funds. At the same time, the necessity of applying neural network modeling in the budget and tax system based on the identification and assessment of risks in order to achieve a balanced state budget is revealed.The value of this research lies in the vision and detailed elaboration of the areas of application of AI in public finance management, focused on improving efficiency and transparency, which ultimately contributes to the well-being of citizens and the prosperity of the country.Key words: artificial intelligence, public finance, budget funds, efficiency, planning, budget non-utilization.